Study of strength characteristics and radiation-protective properties of polystyrene tungsten composite materials - Prokhorenko, E.M.; Lytvynenko, V.V.; Zakharchenko, A.A.; Khazhmuradov, M.A.; Prokhorenko, T.G. (Problems of Atomic Science and Technology, 2023)
Samples of composite materials are made of polystyrene, which is reinforced with dispersed aluminum. The radiation protective additive was powdered tungsten or powdered steel. The tensile strength, for these samples of composites, was investigated. The tensile strength value was obtained at various temperatures. It has been found that the ultimate strength of composites increases with an increase in the metal component. Composites with different component compositions were studied. The relative attenuation of the absorbed dose of gamma radiation by these composite materials has been calculated. Composites were with different mass composition. The code of Geant4 v 4.9.6p03 applied for calculations. It is got, that experimental results coincide with calculation results. Зразки композиційних матеріалів виготовлені з полістиролу, армованого дисперсним алюмінієм. Радіаційно-захисною добавкою був порошковий вольфрам або порошкова сталь. Межу міцності для цих зразків композитів досліджували. Значення межі міцності отримано за різних температур. Знайдено, що межа міцності композитів збільшується із збільшенням металевої компоненти. Вивчалися композити з різним компонентним складом. Проведено розрахунки щодо ослаблення поглиненої дози гамма-випромінювання цими композиційними матеріалами. Композити були iз різним масовим складом. Код Geant4 v 4.9.6p03 застосовували для розрахунків. Отримано, що експериментальні результати збігаються із розрахунковими.